What Determines Audit Quality of the Inspectorate Officials in Regional Financial Supervision? - Darwanis, Darwanis; Putri, Bella Azzahra Suhendra (Universitas Syiah Kuala, 2020)
Objective This study aims to examine the effect of competence, independence, accountability, and work experience on the audit quality of the Inspectorate Apparatus in regional financial supervision with auditor ethics and reward as moderating variables.Design/methodology This study used a sample of all inspectorate auditors in Aceh, Indonesia. The sampling technique used was simple random sampling, which resulted in a sample of 80 auditors from a population of 407 auditors. Hypotheses were tested using Moderated Regression Analysis (MRA).Results The findings prove that competence, independence, accountability, and work experience affect audit quality. Auditor ethics can moderate competence, independence, and accountability for audit quality, but auditor ethics cannot moderate work experience on audit quality. Meanwhile, the reward can moderate competence, independence, accountability, and work experience on audit quality.